Analisis Pendataan Dan Faktor Ketidakikutsertaan Warga Desa Bajak Dalam Berlangganan Layanan Sampah - Ramadhan, Fachrul Rozi; Teresa Aulia Putri; Cindy Andira; Sabrina Bernoza Hanifah; M. Farid Adrian; Rizkika Amelia Putri; Hafidz Rizkian Akbar; Muhammad Fauzan Aziman (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
This study aims to analyze people attitudes and behaviors in managing household waste in Bajak, Teluk Segara. Using a descriptive qualitative approach, data were collected through interviews and observations to understand the factors influencing residents' participation in waste collection services. The findings indicate that low community involvement is influenced by habits, local culture, and perceptions of service quality. Therefore, education and awareness-raising are essential strategies to encourage active participation and reduce the negative impacts of improper waste management.